(untitled) (Gestión y Gerencia, 2023)
Occupational health affects the entire labor spectrum. However, scientific professors and researchers tend to accumulate physical and psychological discomfort, commonly going to the specialist in occupational medicine and, in lesser cases, to the psychologist, since they have somatized and often externalized the problem. This is what motivated the professor and university researcher Samuel Scarpato Mejuto to publish the psychiatric satire "Doctor doctor, 100 strange doctoral stories", where he recreates one hundred meetings between an enthusiastic patient and a very formal psychiatrist. The meta message is to open the communication process permanently, without waiting for concerns to accumulate in our minds that, in turn, can lead to burnout problems in the work or family environment. The author narrates humorously, and his moral is to always dare to defend free thinking and enthusiastic entrepreneurship although science and society still do not understand that the limits of knowledge expand precisely with a certain type of "craziness" and creativity.